Pre-service teachers and study abroad experiences: Don't forget about them when they come home. (March 2020) - Arthur, Nancy; Becker, Sandra; Dressler, Roswita; Crossman, Katherine; Kawalilak, Colleen
Highlights: Learning from study abroad experiences was not uniform, indicating pre-service teachers' level of professional development. The majority of pre-service teachers' reflections post-sojourn remained at the descriptive levels. Reflections at the critical level showed clear implications for teaching and learning practices. Customized reflective practice approaches may better support learning in study abroad programs. Additional structure and facilitation are needed to encourage reflection about future teaching roles and practices.